2019
DOI: 10.1002/pd.5529
|View full text |Cite
|
Sign up to set email alerts
|

High false‐positive non‐invasive prenatal screening results for sex chromosome abnormalities: Are maternal factors the culprit?

Abstract: Objective To explore the impact of maternal sex chromosome aneuploidies (SCAs) and copy number variation (CNV) on false‐positive results of non‐invasive prenatal screening (NIPS) for predicting foetal SCAs. Methods In total, 22 844 pregnant women were recruited to undergo NIPS. Pregnant women with high‐risk of SCAs underwent prenatal diagnosis and maternal copy number variation sequencing (CNV‐seq). Results Among 117 women with high‐risk of SCAs, 72 accepted prenatal diagnosis, 86 accepted maternal CNV‐seq, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 26 publications
3
23
0
Order By: Relevance
“…In our previous study (Zhang et al, 2020), we stated that the prediction of SCAs by NIPS may be interfered by maternal factors, and finding a way to deal with discordant SCA results caused by maternal sex chromosome abnormalities is the largest challenge remaining for NIPS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study (Zhang et al, 2020), we stated that the prediction of SCAs by NIPS may be interfered by maternal factors, and finding a way to deal with discordant SCA results caused by maternal sex chromosome abnormalities is the largest challenge remaining for NIPS.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the values of Z-scores had increased in some false-positive cases for XXX and XXY, which may be associated with maternal X chromosome aneuploids. In our previous study ( Zhang et al, 2020 ), we stated that the prediction of SCAs by NIPS may be interfered by maternal factors, and finding a way to deal with discordant SCA results caused by maternal sex chromosome abnormalities is the largest challenge remaining for NIPS.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudoautosomal region consisted of 2 short segments at both termini of sex chromosomes. There would be errors in sequencing of these locations on X and Y chromosomes because of a short sequencing length of 36 bases [19,20,22]. This may be related to a highly variable amplification of chromosome X due to lower guanosine-cytosine content and loss of X chromosome in aging women, which required further investigation [22,24,30].…”
Section: Discussionmentioning
confidence: 99%
“…Yao et al [40] demonstrated for the first time that maternal genomic materials could affect NIPT accuracy. Afterward, many studies demonstrated that maternal factors could significantly affect the accuracy of NIPT for fetal SCAs [8, [16][17][18][19][20][21][22][23][24]41]. Wang et al [8] reported that maternal X chromosome aneuploidy and mosaicism were responsible for approximately 8.6% of discordant NIPT results for SCAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation